Validity, Reliability, and Responsiveness of a New Device for Measuring Pressure Pain Thresholds - Rodrigo Martín-San Agustín; Javier Guerra-Armas; Alberto Gadea-Blázquez; Elena Millán-Magariños; Borja Tronchoni-Crespo; Iván José Fuentes-Abolafio; Adrian Escriche-Escuder (Journal of Clinical Medicine, 2026)
Background/Objectives The evaluation of treatment effectiveness largely depends on the outcome measures used in the study. Patient-reported outcome measures (PROMs), such as the visual analog scale (VAS), and more objective measures, such as pressure pain thresholds (PPT), are commonly employed to capture pain-sensory profiles and hypoalgesic effects. The NOD is a novel digital algometer designed to assess the PPT. This study aimed to evaluate the validity, reliability, and responsiveness of the NOD algometer using a conventional algometer as a reference instrument for PPT assessment. Methods: A prospective longitudinal study with repeated measures was conducted following the COSMIN recommendations for studies evaluating measurement properties. Healthy participants with latent trigger points were recruited from the University of Valencia, where an experimental pain induction procedure was used to generate transient changes in PPT values and evaluate the responsiveness of the NOD device. The PPT was assessed at four time points: baseline, immediately after the intervention, and at 30 and 60 min post-intervention. Results: A total of 40 participants were included in the study (mean age: 22.0 ± 3.35 years; F = 35%). For concurrent validity, a strong positive association was observed between the reference algometer and NOD (Spearman’s ρ = 0.90, p < 0.001), and the limits of agreement ranged from −1.13 to 1.34 (−25.45% to 30.18%). For reliability, intra-session reliability was good to excellent in both sessions (ICC = 0.825 and 0.859), with a standard error of measurement (SEM = 0.63 to 0.82) and minimal detectable change (MDC = 1.75 to 2.26). For responsiveness, significant reductions in NOD values were observed at all post-intervention time points compared to baseline (p ≤ 0.005). The magnitude of change increased over time, with a standardized response mean (SRM = −0.57 to −0.74) and moderate-to-large effect sizes (Cohen’s d = 0.57–0.73). Conclusions: Our findings indicate that the NOD may be a valid and reliable tool for measuring PPT at latent trigger points in healthy participants. The NOD showed a strong association with a reference algometer and good relative reliability under standardized experimental conditions. The device was also able to detect experimentally induced changes in PPT. Nevertheless, further studies are required to establish its interchangeability with conventional algometers, responsiveness to clinically meaningful change, and applicability in clinical populations.